Tetraploid citrus rootstocks are more tolerant to salt stress than diploid - Saleh, Basel; Allario, Thierry; Dambier, Dominique; Ollitrault, Patrick; Morillon, Raphaël (Comptes rendus. Biologies, 2008)
Citrus trees are subject to several abiotic constraints such as salinity. Providing new rootstocks more tolerant is thus a requirement. In this article, we investigated salt stress tolerance of three tetraploid rootstock genotypes when compared to their respective diploid rootstocks ( Poncirus trifoliata, Carrizo citrange, Cleopatra mandarin). Plant growth, leaf fall and ion contents were investigated. At the end of the experiment, leaf fall was observed only for diploid Poncirus trifoliata plants as well as chlorosis symptoms for Poncirus trifoliata and Carrizo citrange diploid plants. The diploid Cleopatra mandarin plants growth rate was not affected by salt stress and has even been increased for tetraploid Cleopatra mandarin. Ion contents investigation has shown lower accumulations of chloride ions in leaves of the tetraploid plants when compared to diploid plants. Our results suggest that citrus tetraploid rootstocks are more tolerant to salt stress than their corresponding diploid. To cite this article: B. Saleh et al., C. R. Biologies 331 (2008). Les agrumes sont soumis à de nombreuses contraintes abiotiques telles que le stress salin. L'obtention de nouveaux porte-greffe plus tolérants est donc nécessaire. Dans cet article, nous avons comparé le comportement de tolérance au stress salin de trois porte-greffe tétraploïdes avec leurs diploïdes respectifs ( Poncirus trifoliata, citrange Carrizo, mandarinier Cléopâtre). La croissance des plantes, la chute des feuilles et le contenu en ions ont été étudiés. A la fin de l'expérimentation, une chute de feuilles a été observée uniquement pour les Poncirus trifoliata diploïdes, des symptômes de chloroses foliaires n'étant observés que pour les Poncirus trifoliata et Carrizo citrange diploïdes. La croissance des plants de mandariniers Cléopâtre diploïdes n'a pas été affectée par le stress et a même été augmentée pour les mandariniers Cléopâtre tétraploïdes. Les dosages ioniques ont montré que les porte-greffe tétraploïdes accumulaient moins des chlorures foliaires que les diploïdes. Nos résultats suggèrent que les porte-greffe d'agrumes tétraploïdes sont plus tolérants au stress salin que leurs diploïdes respectifs. Pour citer cet article : B. Saleh et al., C. R. Biologies 331 (2008).